Factors affecting stock returns of food and beverage companies - Hadi, Aulia Choirul; Cahyono, Yuli Tri (Proceeding International Conference on Accounting and Finance, 2024)
One of the objectives of capital market investors is return. Investors need to carry out various analyzes in order to get the expected return. This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio, Return on Assets, and Earning Per Share on stock returns in food and beverage sub sector companies listed on the Indonesia Stock Exchange in 2020-2022. This research uses a quantitative approach. The data collection technique uses secondary data, in the form of annual reports of food and beverage sub sector companies from 2020 to 2022. The sampling method uses purposive sampling which was obtained by 21 companies during three years of observation (2020-2022) and there were 59 samples after outliers. Data analysis uses multiple linear regression analysis with classical assumption tests and hypothesis testing. The results showed that Return on Assets has an effect, while the Current Ratio, Debt to Equity Ratio, and Earning Per Share have no effect on stock returns. The implications of this research as a reference for investors before investing shares in a company.